2021
DOI: 10.1108/eemcs-02-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Amma Unavagam: mitigating food insecurity through state sponsored food subsidisation programme

Abstract: Learning outcomes The following are the learning objectives of the case study: to address the problem of urban food insecurity. To facilitate the generation of more employment opportunities and women empowerment through self-help groups (SHGs). To understand the transition from the founder to new leadership provided by Ms J Jayalalithaa. To understand consumer perception and preferences for “Amma canteens”. To appreciate how the case study has added to the historical role of soup kitchens. To address the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Community kitchens can provide relief at such times by offering food at fixed prices. In fact, the canteen survey found that their presence had forced private eateries to reduce their prices [64].…”
Section: Addressing the Food Insecurity Of Migration-prone Hill Commu...mentioning
confidence: 99%
“…Community kitchens can provide relief at such times by offering food at fixed prices. In fact, the canteen survey found that their presence had forced private eateries to reduce their prices [64].…”
Section: Addressing the Food Insecurity Of Migration-prone Hill Commu...mentioning
confidence: 99%